Penerapan Problem Based Learning: Pendekatan Inovatif untuk Peningkatan Hasil Belajar di Kelas - Amirulloh, M. Idham; Habiburrohman, Habiburrohman; El-Yunusi, M. Yusron Maulana (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This research aims to analyze the implementation of the Problem-Based Learning (PBL) model at SMA Wahid Hasyim II Taman. The research focus includes the PBL implementation process, student learning outcomes, and factors that influence the success of PBL implementation. Using a qualitative approach, data was collected through in-depth interviews with PAI teachers and students, classroom learning observations, as well as documentation of learning outcomes and learning planning. The research results show that the implementation of PBL has been effective and has had a positive impact on the learning process and outcomes. Students show improvements in learning activities, critical thinking abilities, and problem-solving skills. The successful implementation of PBL is supported by the selection of authentic problems, teacher readiness in designing learning, and active involvement of students. Even though there are obstacles such as limited time and student adaptation to new learning models, the strategies implemented by teachers have proven to be effective in overcoming these challenges. This research makes an important contribution to the development of problem-based learning practices at the high school level